Find Waldo now - Handford, Martin (Boston : Little, Brown, 1988)
The reader follows Waldo as he travels through different time periods in history and must try to find him in the illustrations of some of crowded events in which he participates.
Col. ill. on lining papers.
First published as: Where's Wally now. London : Walker Books, 1987.
4.7
3-6
Keywords: Humorous stories; Picture puzzles; Time travel -- Fiction; Literary recreations